Strategi Merger Dalam Meningkakan Stabilitas Ekonomi Di Masa Pandemi Covid-19 - Upita Anggunsuri; Shafira Hijriya (Nagari Law Review, 2021)
The government issued several regulations to stimulate the economy that have worsened due to the Covid-19 pandemic. The issuance of Regulation of the Financial Services Authority No. 18/2020 on Written Directives for the Handling of Distressed Banks, so Financial Services Authority has authority to give written directives to financial services institution to do merger, consolidation, acquisition, integration, and conversion. This research aims to analyze the legal implications of the issuance of Regulation of the Financial Services Authority No. 18/2020 on Written Orders for Handling of Distressed Banks, which resulted in monopolistic practices and unfair competition. It is contrary to Law No. 5/1999. This research endeavors to answer the following questions: how the merger strategy to increase economic stability during the Covid-19 Pandemic and the obstacles faced implementing the merger to increase economic stability during the Covid-19 Pandemic, and the efforts that can be made to overcome it. The research method used is juridical normative. The study concludes that the relevant merger strategy approaches to be applied by banks during the pandemic are Horizontal Mergers and Market Extension Merger. The second approach to the merger strategy can be a consideration for banks to implement Regulation of the Financial Services Authority No. 18/2020. The obstacles faced to implement the merger are the Bank's unreadiness in responding to Regulation of the Financial Services Authority No. 18/2020 because the complicated merger process does consider the tangible assets of the banking system and aspects intangible assets. Then, the overlap of several Regulations with the issuance of Regulation of the Financial Services Authority No 18/2020 (the overlap Regulation of the Financial Services Authority No 18/2020 on Written Orders for Handling of Distressed Banks with Law No. 5/1999 on Prohibition of Monopolistic Practices and Unfair Business Competition and Government Regulation No. 57/2010 on Merger or Consolidation of Business Entities and Acquisition of Shares which May Result in monopolistic Practices and Unfair Business Competition). It can have an impact on monopolistic practices and unfair business competition.